2019
DOI: 10.2147/opth.s211337
|View full text |Cite
|
Sign up to set email alerts
|

<p>RE-PERG, a new paradigm for glaucoma diagnosis, in myopic eyes</p>

Abstract: Purpose To evaluate reliability of steady-state pattern electroretinogram (ssPERG) phase variability in re-test (procedure called RE-PERG) in the presence of myopia, which is known to affect ssPERG amplitude, in glaucomatous patients (GP), normal controls (NC), and myopic patients (MY). Methods The procedure was performed on 50 GP, 35 NC, and 19 MY. All subjects were examined with RE-PERG, spectral-domain coherence tomography (SD-OCT), and standard automated perimetry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…[26][27][28] There is, however, a paucity of information of PERG features in patients with both glaucoma and high myopia, with only 1 other study investigating this in the literature. 29 In our observational study, we aimed to investigate the characteristics of ssPERG in subjects with glaucoma and high myopia. The identification of specific ssPERG features may aid in distinguishing between both conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] There is, however, a paucity of information of PERG features in patients with both glaucoma and high myopia, with only 1 other study investigating this in the literature. 29 In our observational study, we aimed to investigate the characteristics of ssPERG in subjects with glaucoma and high myopia. The identification of specific ssPERG features may aid in distinguishing between both conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At the same way, it is also known that age-related visual conditions such as age itself, presbyopia and cataract can influence PERG. As for cataract, we showed reduced amplitude with small intrinsic variability of the phase in a RE-PERG pilot study,[ 57 ] but further studies are required also in the other above-mentioned conditions. Our results suggest that RE-PERG is a quick, easy to perform and non-invasive test able to detect RGC dysfunction in AD, but despite its promise its utility must be confirmed in other laboratories and in larger cohorts of patients.…”
Section: Discussionmentioning
confidence: 88%
“…In previous studies we showed that phase variability is higher in glaucoma patients and that it is not influenced by cataract or myopia. [ 57 , 58 ] Since the neurodegeneration of RGCs shows similar features in glaucoma and AD, we examined the ability of RE-PERG to identify early-stage AD and to discriminate AD from VD on the basis of the different mechanisms of neurodegeneration. The results showed a slightly significant reduction in the PERG Amp value in AD patients vs. NC, but no difference between VD patients and NCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations